Corpus em trânsito: trajetória e formação de um artista-professor de teatro - SILVA, Maurilo Almeida da (2018)
The present research narrates the process of an artist and a teacher´s education and training at the Theater Education undergraduate course from the Federal University of Para (UFPA). Life and artistic experiences deal mutually between individual and collective memories. This work is underpinned theoretically by Le Goff studies on memory (1990); by Cohen on performance (2013); by Boal on theater (2007), and also Rangel´s approach on artistic processes (2009). In this way, the investigation carried out on this work demonstrates the possibility of a broaden approach about means of creation in art/theater under a dialogue between life and art, while creating or re-visiting experiences that value the meeting of those points of knowledge. We emphasize the importance of a research that values and makes possible those transversalities, because it shows spaces for voices that were silenced by time, by places and also by diverse social processes which we are inserted.